Bevacizumab for pediatric radiation necrosis. Issue 4 (20th January 2020) - Baroni, Lorena V; Alderete, Daniel; Solano-Paez, Palma; Rugilo, Carlos; Freytes, Candela; Laughlin, Suzanne; Fonseca, Adriana; Bartels, Ute; Tabori, Uri; Bouffet, Eric; Huang, Annie; Laperriere, Normand; et al.
Abstract: Background: Radiation necrosis is a frequent complication occurring after the treatment of pediatric brain tumors; however, treatment options remain a challenge. Bevacizumab is an anti-VEGF monoclonal antibody that has been shown in small adult cohorts to confer a benefit, specifically a reduction in steroid usage, but its use in children has not been well described. Methods: We describe our experience with bevacizumab use for symptomatic radiation necrosis at 5 institutions including patients treated after both initial irradiation and reirradiation. Results: We identified 26 patients treated with bevacizumab for symptomatic radiation necrosis, with a wide range of underlying diagnoses. The average age at diagnosis of radiation necrosis was 10.7 years, with a median time between the last dose of radiation and the presentation of radiation necrosis of 3.8 months (range, 0.6-110 months). Overall, we observed that 13 of 26 patients (50%) had an objective clinical improvement, with only 1 patient suffering from significant hypertension. Radiological improvement, defined as reduced T2/fluid-attenuated inversion recovery signal and mass effect, was observed in 50% of patients; however, this did not completely overlap with clinical response. Both early and late radiation necrosis responded equally well to bevacizumab therapy. Overall, bevacizumab was very well tolerated, permitting a reduction of corticosteroid dose and/or duration in the majority of patients. Conclusions: Bevacizumab appears to be effective and well-tolerated in children as treatment for symptomatic radiation necrosis and warrants more robust study in the context of controlled clinical trials.